The Effect of Investment Education, Investment Risk, Price Perception, on Interest in Investing in the Capital Market with Investment Motivation as Mediation - Dwi Pranesta, Dhea; Suhardi, Suhardi; Deseria, Rita; Yani, Ahmad (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the factors that influence students' investment intentions in Bangka Belitung, by highlighting the role of investment education, risk perception, price perception, and motivation as mediating variables. Using a quantitative approach with PLS-SEM analysis techniques, data were obtained from 286 students in various universities. The results show that price perception has the most dominant direct influence on investment intentions, indicating students' sensitivity to the affordability aspect. Meanwhile, investment education does not show a significant influence, suggesting the possibility of inappropriate material or delivery methods. Interestingly, risk perception has a positive effect on motivation, which then mediates investment intentions, illustrating that risk is seen as a challenge, not an obstacle. Motivation plays an important role in bridging perceptions to real actions. The socio-cultural context of Bangka Belitung, which is still dominated by traditional investment and limited digital access, reinforces the importance of locally-based financial literacy. This study provides recommendations for designing investment education programs that are contextual, affordable, and able to inspire the younger generation in making rational and sustainable investment decisions.